Foggy Social Structures Irregular Migration, European Labour Markets and the Welfare State - Bommes, Michael; Sciortino, Giuseppe (Amsterdam University Press, 2011)
Irregular migration systems are giving way to an undocumented population in Europe that is estimated at some millions. The migrants manage to live and work for years without a certified identity yet within 'foggy' social structures. What strategies and mechanisms allow them to avoid detection, generate an income and access necessary services? What alternatives are pursued - at whatever human cost - to substitute for political membership and legal protection? How does irregular status impact social interactions? Based on empirical studies carried out across the Continent, this book explores how irregular migration systems developed over time to interact with changing European labour markets, welfare regimes and immigration policies. Foggy Social Structures considers such phenomena one of contemporary society's distinctive features, one that challenges existing notions of political statehood and societal membership.